ANTUSIASME ANAK USIA DINI TERHADAP PERMAINAN TRADISIONAL ENGKLEK PADA ERA TEKNOLOGI KELAS B DI TK BINA INSANI SURABAYA - Hasan, Ade Irmawati; Arif, Muchamad; Muzaqi, Sugito (MOTORIC, 2023)
The research is motivated by researchers' observations of children's enthusiasm for traditional games in today's technological era. This study aimed to determine how enthusiastic kindergartners are toward Engklek, a traditional game, in class B of Bina Insani Surabaya Kindergarten. This research uses descriptive qualitative research methods. Data collection technique by participant observation, interviews, and documentation. The research subject is students of Class B in Bina Insani Surabaya Kindergarten. The research object is children's enthusiasm for the traditional game Engklek. The results of the study show that children's enthusiasm for traditional games varies. The children were enthusiastic about the traditional hopscotch game and most experienced an increase in enthusiasm from the first to the fourth. In this study, it was not found that children were very enthusiastic about the traditional game of cranks where the Berkembang Sangat Baik (BSB) indicator (very good development indicator) was achieved. Keywords: Enthusiasm, Traditional Game, Hopscotch